Total Flavonoids, Antioxidant Capacity, and Metabolite Profiling of Red Ginger (Zingiber officinale var. rubrum) Jahira 1 Variety - Purwanto, Ukhradiya Magharaniq Safira; Athaya, Ardelia; Septaningsih, Dewi Anggraini; Safithri, Mega (Indonesian Journal of Applied Research (IJAR), 2024)
Red ginger (Zingiber officinale var. rubrum) is traditionally recognized for its medicinal properties, largely due to its antioxidant potential attributed to secondary metabolites such as flavonoids. This study aimed to evaluate the total flavonoid content and antioxidant capacity of ethanol and water extracts of red ginger from Sukabumi, specifically the Jahira 1 variety, as well as identify bioactive compounds. Extraction was carried out using the maceration method. The total flavonoid content was determined using the aluminium chloride colorimetric method, while the antioxidant capacity was assessed via the ferric reducing antioxidant power (FRAP) assay. Results showed that the ethanol extract had higher total flavonoid content and antioxidant capacity, with values of 5.99 mg quercetin equivalent (QE)/g and 473.93 µM Trolox equivalent (TE)/g, respectively. In contrast, the water extract exhibited 3.73 mg QE/g and 206.75 µM TE/g. Further LC-MS/MS analysis of the ethanol extract identified 26 compounds, including phenolics and terpenoids, which contribute to the antioxidant capacity of red ginger from Sukabumi.